Signal Transduction in Cancer Metastasis - Wu, Wen-Sheng.; Hu, Chi-Tan.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
The poor prognosis and high mortality for cancer patients are majorly ascribed to tumor metastasis, one of the most complicated pathological processes. Elucidation of molecular mechanisms for metastasis is essential for management and prevention of this lethal condition. In the book to be published, we take comprehensive review in regard with the signal mechanisms responsible for triggering a series of phenotypical changes of primary tumor which may lead to final colonization of the tumor in a second home. Specifically, the initial stage of tumor metastasis will be highlighted. The complex tumor microenvironment accumulate a lot of growth factors, inflammatory cytokines and extracellular matrix which may turn into a group of potent metastatic factors. An integrated and sustained signaling induced by these metastatic factors may trigger EMT, migration and invasion of primary tumor into surround tissue. Blokcade of these signal pathways is the most effective approach for prevention of tumor metastasis. A lot of clinical trials are under way for this purpose and the outcome are promising. The expert reviews compiled in this book may encourage the researcher in this exciting field for future study.
Overview of Signal Transduction in Tumor Metastasis -- Microenvironment Triggers EMT, Migration and Invasion of Primary Tumor via Multiple Signal Pathways -- The ERK1/2 MAP Kinase Signaling Pathway in Tumor Progression and Metastasis -- Mitogen-Activated Protein Kinase-Activated Protein Kinases and Metastasis -- Grb2 and Other Adaptor Proteins in Tumor Metastasis -- The Role of ROS Signaling in Tumor Progression -- Signal Cross Talks for Sustained MAPK Activation and Cell Migration Mediated by Reactive Oxygen Species: The Involvement in Tumor Progression -- Insights into the Dynamics of Focal Adhesion Protein Trafficking in Invasive Cancer Cells and Clinical Implications -- Notch Signaling in Cancer Metastasis -- New Concepts on the Critical Functions of Cancer- and Metastasis-Initiating Cells in Treatment Resistance and Disease Relapse: Molecular Mechanisms, Signaling Transduction Elements and Novel Targeting Therapies -- Involvement of Lipid Rafts in Growth Factor Receptors-Mediated Signaling for Cancer Metastasis -- Cadherin-Catenin Signaling in Ovarian Cancer Progression -- PTP4A3, a Signal Molecule Deregulated in Uveal Melanoma Metastasis -- Signal Transduction Pathways Involved in Hepatocarcinogenesis and Metastasis of Hepatoma.
Keywords: Medicine; Cancer research; Molecular biology; Oncology; Proteins; Cytokines; Growth factors; Cell biology; Medicine & Public Health; Oncology; Cancer Research; Molecular Medicine; Cytokines and Growth Factors; Receptors; Cell Biology; Electronic books